Cloning and Expression of the Nucleocapsid Protein of Newcastle Disease Virus in Pichia Pastoris (Guillierm.) Phaff - Saidin, Syazwan (2010)
Newcastle disease virus (NDV) is the only member of the genus Avulavirus of the family Paramyxoviridae. NDV causes a respiratory disease in birds known as Newcastle disease (ND) which may result in high mortality in susceptible hosts such as chickens leading to substantial loss in the poultry industry. Recent outbreak has been reported in many countries including Malaysia. The continuing treat of ND to the poultry industry requires routine testing through development of better diagnostic tools. Therefore, the objective of the current study was to express the immunogenic nucleocapsid (NP) gene in a Pichia pastoris expression system with a view to develop a potential and cost effective antigen for development of a diagnostic test. In the present study, the gene encoding NP protein of Newcastle disease virus strain AF2240 was cloned into expression vector, pPICZA and placed under the control of methanol inducible alcohol oxidase (AOX) promoter. Then recombinant multi-copy number Pichia cells with Mut+ phenotype were selected for NP protein expression. The optimization of the NP protein production in 50 ml culture was carried out for methanol concentration and different loaded volume in identical shake flask. A time course study for NP production in 250-ml flask with the optimized conditions was performed as well. The result showed that NP protein could be detected after 12 h of methanol induction and the level of protein expression decreased over time. The recombinant NP was purified from the yeast culture using sucrose gradient ultracentrifugation. The high level and intact recombinant nucleocapsid protein expression (570 mg/l) was obtained after 24 h of induction with 1% methanol when 10% of the shake flask was loaded with MMH (minimal methanol with histidine) medium. Western blot analysis using polyclonal NP antibody confirmed the expression of NP with the molecular weight of 53 kDa indicating that NP protein retained its antigenicity. The recombinant NP protein was highly stable in P. pastoris system because there was no degraded product after purification. This result proved that the yeast expression system produces a high yield of recombinant NP protein. The production of recombinant NP protein in bulk as the antigen for diagnostic tools would facilitate the monitoring of NDV infection as well as allowing a more effective control of the disease.